Advancing the understanding of osteosarcoma metastasis: characterizing the impact of exosomes on lung fibroblasts and metastatic colonization - Palmer, Eric Patrick, author; Regan, Daniel P., advisor; Thamm, Doug, committee member; Podell, Brendan, committee member; Redente, Elizabeth, committee member (Colorado State University. Libraries, 2025)
Osteosarcoma (OS) is the most common malignant bone cancer, typically diagnosed in children and young adults. 30-40% of all OS patients develop tumor recurrence that occurs almost exclusively in the form of lung metastasis, which is associated with a dismal 20% 5-year survival rate. Recent evidence suggests organ specific metastasis, organotropism, may be driven by tumor secreted extracellular vesicles called exosomes. Exosomes have been shown to traffic to specific organs where they are taken up by target cells, releasing their biological cargos, and reprogramming those cells towards tumor-promoting phenotypes that alter the microenvironment in advance of circulating tumor cells, thus creating a pre-metastatic niche. Cancer-associated fibroblasts are a critical cell type within the lung TME, which promote immune suppression, drug resistance, and tumor cell survival. Prior work shows tumor cells can co-opt fibroblasts to a pro-tumorigenic phenotype via exosome mediated intercellular communication. Currently, the mechanisms by which OS exosomes modulate resident lung fibroblast function and promote enhanced metastatic colonization of the lung has not been evaluated. To investigate this, we isolated exosomes from a panel of 6 OS cell lines. We assessed the uptake and response of human donor-derived primary lung fibroblasts (LF's; n=4) to OS exosome treatment in vitro via flow cytometry, confocal fluorescent microscopy, proliferation assays, phospho-kinase array, multiplex cytokine analysis and RNA-sequencing. We observed that LFs efficiently take up OS exosomes, which is associated with induction of MAPK pathway activation, fibroblast proliferation and significantly enhanced secretion of IL-6, CXCL8 and CCL2 compared to untreated LFs. RNA-seq of exosome treated LFs confirmed these responses and revealed significant enrichment of pathways related to cytokine secretion, proliferation, immune cell chemotaxis, migration, proinflammatory and profibrotic mediators. Finally, in an exosome-educated lung fibroblast-OS co-culture model, exosome educated LFs conferred significantly increased OS cell survival and proliferation as compared to untreated fibroblasts. To evaluate the impact of OS-derived exosomes on metastatic colonization in vivo, we sought to develop a highly sensitive mouse model of OS metastasis for detection of OS cells by bioluminescent IVIS imaging and spectral flow cytometry. To overcome the lack of universally expressed and distinguishing cell surface markers on OS cells, we evaluated using fluorescent cell labeling dyes, Cell Trace Yellow and DIR. By using a mouse lung resident cell type antibody panel, we determined these dyes are not restricted to the tumor compartment and therefore are likely not useful for tracking OS cells in vivo. Next, using a lentiviral transduction system, we generated a 143b, OS cell line that expressed nuclear red fluorescent protein (RFP) and Luciferase. Here, we demonstrate the use of this reporter system allows for the rapid and highly sensitive detection of OS cells in the lung by bioluminescent imaging and spectral flow cytometry within 24-hours of tumor cell, tail vein injections. Next, we evaluated the impact of repeated intravenous exosome educations on metastatic colonization of the lung using both human OS cell line, 143b in an immunocompromised xenograft mouse model and mouse OS cell line, K7M2, in an immunocompetent syngeneic mouse model. Bioluminescent intravital imaging 4 days post-tumor cell tail vain injections reveal exosomes derived from 143b OS cells but not K7M2 OS cells promoted enhanced metastatic lung colonization efficiency. Based on these observations, we sought to determine if changes in resident mouse lung cell populations and intracellular cell signaling were associated with increased metastatic lung colonization resulting from exosome treatments. By employing a 9-marker, anti-mouse panel, we show no significant changes to resident mouse lung CD45+ or stromal cell populations. Additionally, we observed no changes to lung concentrations of previously identified IL-6 and CCL2 upon exosome education. However, follow up studies would show tumor cell involvement may be required to stimulate significant changes to cell populations and cell signaling within this model. Finally, despite observations that OS exosomes can induce striking changes to lung fibroblasts in vitro and promote metastatic colonization in vivo, we did not observe any significant differences in overall survival among mice exposed to OS exosomes prior to tumor cell injection. Taken together, we show OS-derived exosomes can induce lung fibroblasts to shift towards a tumor-promoting phenotype in vitro. Additionally, chronic exosome treatments promote metastatic colonization in an immunocompromised xenograft mouse model. However, these findings were not correlated to alterations among resident lung cell populations, tumor-promoting intracellular signaling molecules, or overall survival.
Keywords: lung fibroblasts; osteosarcoma; exosomes; pre-metastatic niche; lung metastasis